Modelling of Steel-Concrete Composite Structures in Fire Using OpenSees. Issue 2 (February 2014) - Jiang, Jian; Usmani, Asif; Li, Guo-Qiang
This paper presents the extension of the structural analysis software framework OpenSees for modeling steel framed composite structures subjected to fire including the development of a geometrically nonlinear shell element. The new shell element is formed by a combination of membrane elements and Mindlin plate bending elements using a general total Lagrangian formulation. The MITC technique (Mixed Interpolation of Tensorial Components) is applied to alleviate shear locking problems and the addition of drilling degrees of freedom is included. A new thermal load class was created to define the temperature distribution through the thickness of the shell section. The two-dimensional OpenSees material, DruckerPrager, was modified to model the concrete in the composite deck slab at elevated temperature with temperature-dependent material properties according to the Eurocode 2. A three-dimensional finite element model of a composite structure was built in OpenSees, consisting of a flat reinforced concrete slab modeled by the developed shell element as well as concrete ribs and beams/columns modeled by three-dimensional beam elements. These components were connected by rigid link elements to model composite action. The performance of the developed model is verified and validated by a series of analytical solutions and experimental results respectively. Among these are: one-way bending of steel plates; fire tests on simply supported composite beams; and reinforced concrete slabs where membrane actions are investigated. Cardington restrained beam test and British Steel Corner test are also modeled. The reasonable agreement achieved between OpenSees predictions and experimental measurements shows the validity of the developed OpenSees extension to model composite structures in fire. The horizontal displacement of the column at floor level was modeled for the first time with reasonable agreement. This work is part of a wider project which, upon completion, will provide a user-friendly open-source computational platform for structural fire engineering analyses from fire dynamic simulation through to heat transfer analysis and mechanical analysis.